State control and the effects of foreign relations on bilateral trade - Davis, Christina L.; Fuchs, Andreas; Johnson, Kristina (The journal of conflict resolution, 2019)
Can governments still use trade to reward and punish partner countries? While World Trade Organization (WTO) rules and the pressures of globalization restrict states’ capacity to manipulate trade policies, politicization of trade is likely to occur where governments intervene in markets. We examine state ownership of firms as one tool of government control. Taking China and India as examples, we use new data on bilateral trade disaggregated by firm ownership type as well as measures of political relations based on bilateral events and United Nations voting data to estimate the effect of political relations on import flows since the early 1990s. Our results support the hypothesis that imports controlled by state-owned enterprises are more responsive to political relations than imports controlled by private enterprises. This finding suggests that politicized import decisions will increase as countries with partially state-controlled economies gain strength in the global economy. Extending our analysis to exports for comparison, we find a similar pattern for Indian but not for Chinese exports and offer potential explanations for these differential findings.